[BEDT-TTF][Fe(C2O4)Cl2]: an organic–inorganic hybrid semiconductive antiferromagnet. Issue 42 (27th June 2016) - Zhang, B.; Zhang, Y.; Wang, Z.; Yang, D.; Gao, Z.; Wang, D.; Guo, Y.; Zhu, D.; Mori, T.
Abstract : A radical cation salt composed of an organic donor BEDT-TTF 1.0+ and a one-dimensional inorganic anion [Fe(C2 O4 )Cl2 − ] n was obtained by electrocrystallization. Abstract : A radical cation salt composed of an organic donor, BEDT-TTF 1.0+, and a one-dimensional inorganic anion, [Fe(C2 O4 )Cl2 − ] n, was obtained by electrocrystallization, and was identified as a semiconductor with values of σ 300K = 3.0 × 10 −5 S cm −1 . Spin-canted antiferromagnetic long-range ordering was observed at 5.5 K from ZFCM/FCM/RM measurement and confirmed using AC measurement.